A clinical study of genetic testing to guide the dosing of warfarin after heart valve replacement - Fan Zhang; Congcong Zhang; Chengxiong Gu; Yang Yu; Jingxing Li (BMC Cardiovascular Disorders, 2022)
Abstract Objective To explore the role of genetic testing of VKORC1 and CYP2C9 in determining the dosage of warfarin after aortic valve replacement. Methods A total of 172 patients receiving warfarin after aortic valve replacement were divided into a control group (n = 86) and an experimental (n = 86) group based on acceptance of genetic testing. In the experimental group, three loci of VKORC1 and CYP2C9 were tested by polymerase chain reaction-restriction fragment length polymorphism technique, and the initial dose of warfarin was determined based on the genetic testing results and warfarin oral-dose table recommended by U.S. Food and Drug Administration (FDA). In the control group, warfarin (3 mg per night) was used as the initial dose. The international normalized ratio (INR) of each patient was continuously monitored after medication. The percentages of patients meeting the target INR in the two groups at specific time points and at 3-month follow-up after discharge from the hospital were monitored, and the incidence of various adverse events was compared between the groups. Results Based on the results of genetic testing, 68 patients received 3–4 mg/d (79.1%), 10 patients received 0.5–2 mg/d (11.6%), and eight patients received 5–7 mg/d (9.3%) as the initial dosages of warfarin in the experimental group. The percentages of the patients meeting the target INR on the third and sixth day of postoperative medication were 45.3% and 73.3%, respectively, in the experimental group, and 29.8% and 58.3%, respectively, in the control group. The INR critical values during hospitalization occurred in 2.3% in the experimental group and in 7.1% in the control group, while the percentage of the patients meeting the target INR after 3 months was 86.1% in the experimental group and 83.1% in the control group. Conclusion Genetic testing may guide the selection of the initial dose of warfarin after heart valve replacement to rapidly achieve a stable dose.